Effectiveness of myopia control interventions: A systematic review of 12 randomized control trials published between 2019 and 2021 - Lanca, Carla; Pang, Chi Pui; Grzybowski, Andrzej (Frontiers in Public Health, 2023)
Purpose: This study aims to investigate the effectiveness of interventions to control myopia progression. In this systematic review, the primary outcomes were mean differences (MD) between treatment and control groups in myopia progression (D) and axial length (AL) elongation (mm). Results:The following interventions were found to be effective (p<0.001): highly aspherical lenslets (HAL, 0.80 D, 95% CI, 0.77-0.83; -0.35 mm, 95% CI -0.36 to -0.34), MiSight contact lenses (0.66 D, 95% CI, 0.63-0.69; -0.28 mm, 95% CI-0.29 to -0.27), low dose atropine 0.05% (0.54 D, 95% CI, 0.38-0.70; -0.21 mm, 95% CI-0.28 to -0.14), Biofinity +2.50 D (0.45 D, 95% CI, 0.29, 0.61; -0.24 mm, 95% CI -0.33 to -0.15), defocus incorporated multiple segments [DIMS] (0.44 D, 95% CI, 0.42-0.46; -0.34 mm, 95% CI -0.35 to -0.33) and ortho-k lenses (-0.24 mm, 95% CI -0.33 to -01.5). Conclusions: Low-dose atropine 0.01% was not effective in reducing AL progression in two studies. Treatment efficacy with low-dose atropine of 0.05% showed good efficacy. Spectacles (HAL and DIMS) and contact lenses (MiSight and Biofinity) may confer a comparable treatment benefit compared to atropine, to slow myopia progression.